Cloning and Molecular Characterization of the Schistosoma mansoni Genes RbAp48 and Histone H4 - Patrícia P Souza; Débora N Santos; Sérgio D J Pena; Glória R Franco (Memorias do Instituto Oswaldo Cruz, 2002)
The human nuclear protein RbAp48 is a member of the tryptophan/aspartate (WD) repeat family, which binds to the retinoblastoma (Rb) protein. It also corresponds to the smallest subunit of the chromatin assembly factor and is able to bind to the helix 1 of histone H4, taking it to the DNA in replication. A cDNA homologous to the human gene RbAp48 was isolated from a Schistosoma mansoni adult worm library and named SmRbAp48. The full length sequence of SmRbAp48 cDNA is 1036 bp long, encoding a protein of 308 amino acids. The transcript of SmRbAp48 was detected in egg, cercariae and schistosomulum stages. The protein shows 84% similarity with the human RbAp48, possessing four WD repeats on its C-terminus. A hypothetical tridimensional structure for the SmRbAp48 C-terminal domain was constructed by computational molecular modeling using the b-subunit of the G protein as a model. To further verify a possible interaction between SmRbAp48 and S. mansoni histone H4, the histone H4 gene was amplified from adult worm genomic DNA using degenerated primers. The gene fragment of SmH4 is 294 bp long, encoding a protein of 98 amino acids which is 100% identical to histone H4 from Drosophila melanogaster.